'The Sister' in the Early Days of the Nhs. Issue 4 (April 2016) - Ellis, Harold
All the readers of this journal will have read and heard about the ward and operating theatre sisters in 'the old days'. What were they really like, and what was it like to work with them in the hospitals of those far-off times? I entered the old Radcliffe Infirmary Oxford in the summer of 1945, just as World War II was drawing to a close, as a 19 year old student to start my clinical training. I then qualified in July 1948, the very month the NHS came into being, and started my surgical career as house surgeon. The Radcliffe was the only acute hospital in the town and dealt with all emergency admissions. In addition, we worked at the Churchill Hospital, then a hutted hospital, erected during the War to deal with Canadian military casualties and now handed over for civilian use. Elective orthopaedics was carried out at the Wingfield Morris Hospital, later the Nuffield Orthopaedic Centre. The patients here were mostly children with bone and joint tuberculosis or poliomyelitis. The Slade Isolation Hospital dealt with the infectious fevers; I was admitted there twice as a student, with first chicken pox and then measles, both caught from my patients!